The importance of health-related physical fitness - Maria Fátima Glaner (Universidade Federal de Santa Catarina, 2003)
Mechanization and automation, swift communication and transport, computer usage and television viewing have reduced the need for vigorous occupations and discouraged involvement in leisure-time recreational activity. Studies have reported that there is a causal relationship between the risk of chronic disease incidence and mortality and physical activity and/or physical fi tness. Therefore, the aim of this review is to summarize and synthesize the association between health-related physical fi tness (aerobic endurance, fl exibility, strength/ endurance, body fat) and chronic diseases. The papers reviewed demonstrate that higher and moderate levels of aerobic endurance, fl exibility, muscular strength/endurance, and desirable body fat levels, are very important for promoting health at all ages, and to avoid early development of chronic diseases. RESUMO A mecanização e a automação, o transporte e a comunicação rápidos, o uso do computador e da televisão têm diminuído atividades vigorosas, inclusive no tempo livre. Estudos reportam que a relação entre o risco de incidência de doenças crônico-degenerativas e a atividade física e/ou a aptidão física é causal. Portanto, o objetivo desta revisão é resumir e sintetizar a associação entre aptidão física relacionada à saúde (aptidão cardiorrespiratória, fl exibilidade, força/resistência muscular e gordura corporal) e as doenças crônicodegenerativas. Os estudos mostram que altos e moderados níveis de aptidão cardiorrespiratória, fl exibilidade, força/resistência muscular, e um nível adequado de gordura são muito importantes para promover a saúde em todas idades, bem como evitar o desenvolvimento precoce de doenças crônico-degenerativas.